Clinical features of infantile hepatic hemangioendothelioma - Eun Hee Kim; Kyung Nam Koh; Meerim Park; Bo Eun Kim; Ho Joon Im; Jong Jin Seo (Korean Pediatric Society, 2011)
PurposeInfantile hepatic hemangioendothelioma (IHHE) is the most common type of hepatic vascular tumor in infancy. We conducted this study to review our clinical experience of patients with IHHE and to suggest management strategies.MethodsWe retrospectively analyzed the medical records of 23 IHHE patients (10 males, 13 females) treated at the Asan Medical Center between 1996 and 2009.ResultsMedian age at diagnosis was 38 days (range, 1 to 381 days). Seven patients (30%) were diagnosed with IHHE based on sonographically detected fetal liver masses, 5 (22%) were diagnosed incidentally in the absence of symptoms, 5 (22%) had congestive heart failure, 3 (13%) had skin hemangiomas, 2 (9%) had abnormal liver function tests, and 1 (4%) had hepatomegaly. All diagnoses were based on imaging results, and were confirmed in three patients by histopathology analysis. Six patients were observed without receiving any treatment, whereas 12 received corticosteroids and/or interferon-alpha. One patient with congestive heart failure and a resectable unilobar tumor underwent surgical resection. Three patients with congestive heart failure and unresectable tumors were managed by hepatic artery embolization with/without medical treatment. At a median follow-up of 29 months (range, 1 to 156 months), 21 (91%) patients showed complete tumor disappearance or >50% decrease in tumor size. One patient died due to tumor-related causes.ConclusionIHHE generally has a benign clinical course with low morbidity and mortality rates. Clinical course and treatment outcome did not differ significantly between medically treated and non-treated groups. Surgically unresectable patients with significant symptoms may be treated medically or with hepatic artery embolization.